Aromatization of n-hexane: Synergism afforded by C1-C3 alcohols. (18th May 2020) - Mahale, Rohit S.; Parikh, Parimal A.
Highlights: Hexane and C1-C3 alcohols were aromatized separately and in combination. Presence of alcohol increases carbon yield from hexane. Hexane impedes carbon from alcohol for aromatization. Propanol was most efficient to bring carbon from hexane to aromatics. Dealuminated GaZn-ZSM-5 showed high catalyst life. Abstract: Relatively inexpensive straight chain alkane (hexane), methanol manufactured from abundantly available natural gas, and biorenewably obtainable ethanol have been converted into value-added aromatics. For comparison purposes, propanol too was studied. Catalysts employed include parent ZSM-5, GaZn-ZSM-5 and dealuminated GaZn-ZSM-5; 5 wt.% each of Ga and Zn. Reactions were carried at 3 MPa pressure, 500 °C and with nitrogen as carrier gas. Zeolite dealumination helped increase liquid yields. Liquid products contained only aromatics in addition to unconverted reactants. Presence of an alcohol in general brought more carbon atoms from hexane into aromatics. Propanol showed highest efficiency to aromatize hexane. Dealuminated GaZn-ZSM-5 afforded 100% alcohol conversion even at 28 h time-on-stream, whereas hexane conversion dropped to 80% during this period. Catalyst deactivated due to coke deposition arising from hexane cracking. Soft coke contained oxygenated hydrocarbons with carbon number from C6 to C27 .